Thermo-mechanically-consistent phase-field modeling of thin film flows - Miles, Christopher; van der Zee, Kristoffer George; Hubbard, Matthew E.; Mackenzie, Roderick (Springer, 2018)
We use phase-field techniques coupled with a Coleman-Noll type procedure to derive a family of thermomechanically consistent models for predicting the evolution of a non volatile thin liquid film on a flat substrate starting from mass conservation laws and the second law of thermodynamics, and provide constraints which must be met when modeling the dependent variables within a constitutive class to ensure dissipation of the free energy. We show that existing models derived using different techniques and starting points fit within this family. We regularise a classical model derived using asymptotic techniques to obtain a model which better handles film rupture, and perform numerical simulations in 2 and 3 dimensions using linear finite elements in space and a convex splitting method in time to investigate the evolution of a flat thin film undergoing rupture and dewetting on a flat solid substrate.